Primary Mammary-Analogue Secretory Carcinoma of the Lung: A Rare Entity With an Unusual Location. (October 2020) - Ramos, Josean; Mahmud, Waqas; Ocampo, Fernando Alekos; Alex, Gillian; Gattuso, Paolo
This is a case of a 55-year-old female with past medical history of tobacco smoking, hypertension, and lupus who presented with a left lung nodule, found on computed tomographic scan of the chest during workup for a recently diagnosed squamous cell carcinoma in a cervical lymph node. Resection of the lung nodule showed a 2.3-cm well-defined pale-tan mass, and histologic examination showed a well-circumscribed lesion with papillary, solid, and gland-like architectural patterns, with eosinophilic secretions, areas of comedonecrosis, and increased mitotic activity. Immunohistochemical stains showed the lesion to be positive for cytokeratin 7, S100 protein, and focally positive for mammaglobin. Fluorescence in situ hybridization studies confirmed rearrangement of the ETV6 gene at 12p13.2. To date, our case is the second reported case of a primary mammary-analogue secretory carcinoma arising in the lung, and the first to show evidence of tumor necrosis: an unusual feature in an unusual location.